Estudio de factibilidad para la creación de una agencia de niñeras que brinde un servicio las 24/7 en la ciudad de Cali - Mina López, Jennyfer; Anturi Quintero, Linda Esmeralda (Universidad Antonio Nariño, 2021)
The present research project establishes the feasibility of creating a nanny agency that provides a 24/7 service in the city of Cali. To this end, a market study was carried out, which allowed a market approach to be made for socioeconomic strata 4, 5 and 6, A sample of 390 parents living in the Vipasa, El Ingenio and Parcelaciones Pance nighbourhoods of the city of Cali was taken from the survey and the results were positive, certifying the existence of an unsatisfied demand that is willing to pay for a comprehensive, specialized and personalized service; Next, a technical, organizational and legal study was carried out, in which the tangible and intangible requirements were established, as well as the design of the necessary administrative structure that will allow the project to be executed in a satisfactory manner; finally, a financial study was carried out in which estimated the costs involved in executing the operation, also projecting a budget of possible income, which finally shows that the business is not profitable through financial indicators such as the internal rate of return and the current value. Net, which concludes that the project is not feasible.